The attitude of complete denture wearers towards denture adhesives in Istanbul - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2004)
The purpose of using denture adhesives is to subjectively benefit denture-wearers with improved fit and comfort of their dentures and to improve their chewing ability and confidence. The purpose of this study was to investigate the approach and thought of complete denture wearers to denture adhesives and to see why they had tried denture adhesive, and their reasons for its current use or non-use through a questionnaire. One hundred and fifteen patients attending the Marmara University, Dental School for new denture treatment were surveyed. In the survey, there were 62 females (54%) and 53 males (46%). Nearly half of these patients (53%) were in the 61-70-year age group with a mean age of 64 years. One hundred and six (92%) patients had never tried denture adhesive. Most patients (73%) who did not use denture adhesives managed their dentures well, but a significant number 101 (87%) did not know that denture adhesives existed. Nine (8%) had tried denture adhesives, and none of the patients were currently using them. Those who ceased using denture adhesive complained mainly that it did not improve the fit and chewing ability significantly. The outcome of this survey demonstrated that the knowledge of the patients is not enough on denture adhesives in Istanbul as it is still generally believed by the practitioners that the prescription of a denture adhesive is a sign of failure of the dentist.
Keywords: denture adhesives; dentures